ERROR ANALYSIS OF ELEVENTH GRADE ODD MIDTERM EVALUATION IN VOCATIONAL SCHOOL MUHAMMADIYAH 2, TANGERANG - Woro Endah Sitoresmi; Velma Alicia (BASIS (Bahasa dan Sastra Inggris), 2019)
The objective of this study is to know the grammatical errors and to elaborate the sources of errors in odd midterm evaluation of eleventh grade for the academic year 2018/2019 in Vocational School, Muhammadiyah 2, Parung Serab, Kota Tangerang, Banten. It belongs to descriptive qualitative study which used document analysis to proceed the data. The findings showed that there are five error grammatical items which include tenses (present tense & past continuous tense), preposition, object pronoun, article and quantifier. In addition, there are three sources of errors in the study; error related to context of learning, intralingual error and interlingual error.